Nutritional status, pulmonary functions, and exercise performance in COPD cases - Deveci, Figen; Tug, Tuncer; Turgut, Teyfik; Ogeturk, Murat; Kirkil, Gamze; KaAr, Canan; Muz, M. Hamdi (Turkish Assoc Tuberculosis & Thorax, 2005)
The aim of this study was evaluation of nutritional status in attack and stable chronic obstructive pulmonary disease (COPD) cases, and investigating the relation between nutrition parameters and pulmonary functions, exercise performance and general healthy status. Anthropometric measures of 10 cases with attack (group 1), 14 stabilized COPD cases (group 2) and 10 control cases (group 3) were evaluated by measuring serum albumin, transferrin, tumor necrosis factor-alpha (TNF-a) levels, and fat-free mass (FFM) levels. Six minutes walking test (mwt) and SGRQ questionnaire were performed. Body mass index (BMI) of group 1 and 2 were significantly lower than group 3 (p=0.023, p=0.008, respectively). Albumin levels were significantly lower in group 1 than group 2 (p<0.001) and 3 (p=0.001). Levels of transferrin were significantly lower in group 1 compared with group 3 (p=0.015). TNF-a levels were significantly high in group 1 compared with group 2 (p=0.002), and high in group 2 compared with group 3 (p=0.001). FFM was significantly low in group 1 compared with group 2 (p=0.003), and low in group 2 compared with group 3 (p<0.001). Mean distance of 6 mwt was 225.80+/-40.35 m in group 1, it was 405.16+/-95.51 m in group 2 (p<0.001). A positive relation was seen between FFM and BMI, 6 mwt (p=0.006, r=0.481 ve p<0.001, r=0.830, respectively), between albumin levels and 6 mwt (p<0.001, r=0.850). A negative correlation was observed between TNF-a and 6 mwt (p<0.001, r=-0.745). There was no statistical difference in antropometric measures between groups. Total score and daily life were statistically high in group 1 than group 2 (p= 0.009, p=0.013). Although no changes was seen in antropometric measures of COPD cases, a nutritional defect was seen and a significant relation was observed between nutrition parameters and effort capacity.
KOAH olgularinda beslenme durumu, solunum fonksiyonlari ve egzersiz performansi.
Keywords: COPD; nutrition; respiratory functions; anthropometric measures